STUDENT ENGAGEMENT ON THE IMPLEMENTATION OF ONLINE ENGLISH LEARNING - Putri, Ni Putu Werdhi; Hadi Saputra, I Nyoman Pasek; Pratiwi, Ni Putu Astiti (Universitas Pendidikan Ganesha, 2021)
The English teacher does not involve a net meeting during online English learning. The net meeting is vital because it becomes a space for students to communicate and interact with their friends and teachers. It can trigger feelings, and they do not want to be actively involved in learning English online because they cannot experience the actual teaching experience and interact with their peers and teachers directly. This study aims to analyze student interactions and the difficulties involved in online English learning. This research uses mixed research methods by following a sequential explanatory research design. The sample in this study consisted of 140 students and was selected using the cluster random sampling technique. The process of collecting data in this study was carried out by distributing questionnaires and conducting interviews. The results of this study indicate that the involvement of students during online English learning is included in the high level seen from every aspect. However, there are some difficulties involved in learning English online, including internet connection problems, boredom, and loss of concentration, which psychologically affect motivation. Then, the slow response makes it difficult for students to contract online. In addition, the limited knowledge of English and the lack of direct interaction with the teacher, which makes students understand English subject matter independently, and the lack of direct interaction with fellow students also establish friendships with other students.